The Potential Impact of Employment Policy on the Unemployment Rate Consistent with Nonaccelerating Inflation - Johnson, George E.; Blakemore, Arthur E. (American Economic Review, 2016)
During the past few years there has been considerable interest, among both economists and politicians, in the question of how to lower the unemployment rate consistent with nonaccelerating inflation by the use of structural policies. Although it is not possible to estimate the value of this rate (which will hereafter be referred to as U* ) with any precision, its consensus estimate in 1978 terms is about 6 percent, plus or minus one-half of 1 percent. While recognition of this constraint on aggregate macro-economic policy has been taking hold, Congress has been debating a bill to establish a 4 percent overall unemployment rate as the national goal for 1983. Implicit in this bill (the socalled Humphrey-Hawkins proposal) is the necessity of expanding labor market programs in order to achieve its principal objective. The major component of such programs in the United States has been the direct provision of job opportunities to specific groups in the labor force.' These generally take the form of public service employment (PSE), but there has also been some use of employment tax credits in the private sector. There are several possible objectives of employment policy, ranging from fiscal relief for local governments to a substitution of subsidized employment for welfare. The purpose of this paper, however, is to examine the potential of employment policy to lower U*, i.e., to shift the long-run Phillips curve to the left.2 Can the provision of a large number of PSE jobs or the extensive use of wage subsidies alter the relationship between labor market tightness and the overall unemployment rate such that a lower unemployment can be sustained by macro-economic policy without accelerating inflation? The answer to this question depends on how individual labor markets work-in particular, on the nature of unemployment among the persons toward whom the unemployment programs are targeted. There is little consensus among labor economists about the functioning of these markets and, accordingly, the question of the probable impact of employment policy on U* is subject to considerable controversy. It is therefore useful to frame the issue in a manner which permits empirical testing. Such an attempt, as well as the associated empirical results, is presented in Section I of the paper. Some qualifications to these results, empirical and conceptual, are discussed in Section II.